A framework to update Hofstede's cultural value indices: economic dynamics and institutional stability - Tang, Linghui; Koveos, Peter E (Journal of International Business Studies, 2008)
This study offers an update of the Hofstede cultural value dimensions. We argue that changes in economic conditions are the source of cultural dynamics, while the endurance of institutional characteristics provides the foundation for cultural stability. It is found that national wealth, measured by GDP per capita, has a curvilinear relationship with individualism, long-term orientation, and power distance scores. Relatively speaking, uncertainty avoidance and masculinity mainly reflect some rather stable institutional traditions, such as language, religion, climate, ethnic homogeneity, and legal origin, and are less likely to change over time.